A nonhuman primate model of vertical sleeve gastrectomy facilitates mechanistic and translational research in human obesity - Julia L. Nugent (Elsevier, 2021)
Summary: The obesity epidemic significantly contributes to overall morbidity and mortality. Bariatric surgery is the gold standard treatment for obesity and metabolic dysfunction, yet the mechanisms by which it exerts metabolic benefit remain unclear. Here, we demonstrate a model of vertical sleeve gastrectomy (VSG) in nonhuman primates (NHP) that mimics the complexity and outcomes in humans. We also show that VSG confers weight loss and durable metabolic benefit, where equivalent caloric intake in shams resulted in significant weight gain following surgery. Furthermore, we show that VSG is associated with early, weight-independent increases in bile acids, short-chain fatty acids, and reduced visceral adipose tissue (VAT) inflammation with a polarization of VAT-resident immunocytes toward highly regulatory myeloid cells and Tregs. These data demonstrate that this strongly translational NHP model can be used to interrogate factors driving successful intervention to unravel the interplay between physiologic systems and improve therapies for obesity and metabolic syndrome.